If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 75 = (x) + (x + 5) + (x + 10) + (x + 15) + (x + 20) + (x + 25) 75 = x + (x + 5) + (x + 10) + (x + 15) + (x + 20) + (x + 25) Reorder the terms: 75 = x + (5 + x) + (x + 10) + (x + 15) + (x + 20) + (x + 25) Remove parenthesis around (5 + x) 75 = x + 5 + x + (x + 10) + (x + 15) + (x + 20) + (x + 25) Reorder the terms: 75 = x + 5 + x + (10 + x) + (x + 15) + (x + 20) + (x + 25) Remove parenthesis around (10 + x) 75 = x + 5 + x + 10 + x + (x + 15) + (x + 20) + (x + 25) Reorder the terms: 75 = x + 5 + x + 10 + x + (15 + x) + (x + 20) + (x + 25) Remove parenthesis around (15 + x) 75 = x + 5 + x + 10 + x + 15 + x + (x + 20) + (x + 25) Reorder the terms: 75 = x + 5 + x + 10 + x + 15 + x + (20 + x) + (x + 25) Remove parenthesis around (20 + x) 75 = x + 5 + x + 10 + x + 15 + x + 20 + x + (x + 25) Reorder the terms: 75 = x + 5 + x + 10 + x + 15 + x + 20 + x + (25 + x) Remove parenthesis around (25 + x) 75 = x + 5 + x + 10 + x + 15 + x + 20 + x + 25 + x Reorder the terms: 75 = 5 + 10 + 15 + 20 + 25 + x + x + x + x + x + x Combine like terms: 5 + 10 = 15 75 = 15 + 15 + 20 + 25 + x + x + x + x + x + x Combine like terms: 15 + 15 = 30 75 = 30 + 20 + 25 + x + x + x + x + x + x Combine like terms: 30 + 20 = 50 75 = 50 + 25 + x + x + x + x + x + x Combine like terms: 50 + 25 = 75 75 = 75 + x + x + x + x + x + x Combine like terms: x + x = 2x 75 = 75 + 2x + x + x + x + x Combine like terms: 2x + x = 3x 75 = 75 + 3x + x + x + x Combine like terms: 3x + x = 4x 75 = 75 + 4x + x + x Combine like terms: 4x + x = 5x 75 = 75 + 5x + x Combine like terms: 5x + x = 6x 75 = 75 + 6x Add '-75' to each side of the equation. 75 + -75 = 75 + -75 + 6x Combine like terms: 75 + -75 = 0 0 = 75 + -75 + 6x Combine like terms: 75 + -75 = 0 0 = 0 + 6x 0 = 6x Solving 0 = 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 0 + -6x = 6x + -6x Remove the zero: -6x = 6x + -6x Combine like terms: 6x + -6x = 0 -6x = 0 Divide each side by '-6'. x = 0 Simplifying x = 0
| 5y+6+2y-14=-4y+1+10y | | (x-3)(x+5)=-12 | | 5x+32=9-x | | 20x+18=100 | | 4t-3(t-2)=t+6 | | 3x+71=6x+2 | | .3x-.2=1 | | 3+0.666666666667m=0.666666666667m-0.666666666667 | | a*5+9b=-b+2 | | 5a^2+17a+6=0 | | x-9=-14 | | 1+15n=0 | | 7x-8=9x+3 | | -34=D+42-5v | | -2+.40(5x-20)=-52 | | 3(3n-1)=3(n+11) | | 0.4(2x-4)=-17 | | 4=(3)(-3)+b | | 3w+8=5w-20 | | -3(3y-2)=42 | | 23x-25=21 | | 81x^2-90x+25=0 | | 5n-5/3=n+1 | | 6x+7=52 | | 880=-2+14(-5n+13) | | -6=-18 | | 10x^2y^3(10xy^8)= | | 8-(3+b)=b-19 | | -34=u | | 24=2x+10 | | 114000=1.5x^2 | | 2(3-2(x+5))=30 |